An integrative analysis of workforce agility of police officers - R.S, Harikrishnan; Suresh, M (International Journal of Engineering and Technology, 2018)
The adaptive evolution in relation with the dynamics in the environment is inevitable for an organization to grow and keep up the pace. Or-ganizational intelligence is a crucial factor for such a growth. It is known that workforce agility is related with Organizational intelligence. This paper tries to find the factors influencing on workforce agility amongst the police officers in India. The methodology employed for the study is interpretive structural modelling (ISM). For the case study purpose, the data has taken from the selected police officers from the state of Kerala,India. The paper concluded that the wok experience, age, health condition and work environment are the crucial factors which influences the workforce agility.Â Â Â